Roots, Tubers and Bananas Contributions to Food Security Article - Kennedy, Gina; Raneri, Jessica Evelyn; Stoian, Dietmar; Attwood, Simon; Burgos, G.; Ceballos, Hernán; Ekesa, Beatrice; Johnson, Vincent; Low, Jan W.; Talsma, Elise F. (Elsevier, 2019)
The class of root, tuber and banana (RTB) crops encompasses banana and plantain, cassava, potato, sweet potato, taro, yam and a number of lesser cultivated and consumed root and tuber crops. RTB are the second most important group of crops in LDCs after cereals. RTB are vital for food security, with parts of sub-Saharan Africa, Asia and Latin America relying on RTB as main staple foods in their diets. They provide up to 15% or more of the daily per capita dietary energy for the 763 million people living in the least developed countries. Production, yield and area planted for most RTB are showing increasing trends. While most RTB are used for food, feed and biofuel uses are growing. With vast genetic diversity RTB play an important role in the food systems of countries worldwide. The CGIAR has been actively working within this genetic diversity to improve the nutritional content of some RTB. Most notably varieties of banana, cassava and sweet potato have been successfully identified for higher pro-vitamin A content, while potatoes with higher iron and zinc content are also available. The use of varieties with higher pro-vitamin A, iron and zinc will contribute to reductions in micronutrient deficiencies. Many of the leaves of RTB, most notably cassava and sweet potato are also consumed, sometimes in large amounts and contribute to both diversity of the diet as well as increased intake of essential micronutrients. Threats from pests and disease to which these crops are susceptible are among the largest concerns. The impact of changing climate on resistance to disease/pest threats as well as yield and longer-term sustainability issues is also of concern. Finally, greater research and development on propagation and post-harvest storage and processing is needed for some of the lesser RTB crops.